COMPARISON OF LEGAL PERSPECTIVES OF DIGITAL FINANCING AGREEMENTS BASED ON ISLAMIC CONTRACT LAW AND AGREEMENT LAW IN THE INDONESIAN CIVIL CODE - Lestari, Nur Melinda; In'amullah, Muhammad (Universitas Muhammadiyah Prof DR HAMKA, 2025)
Research Aims: The purpose of this study is to analyze the legal framework required to regulate the implementation of financial technology (fintech), particularly peer-to-peer lending platforms, in order to protect the public from illegal digital financing practices. This study highlights the importance of aligning positive law especially contract law under the Civil Code with Islamic contract law principles, given that many existing digital financing practices minimally apply sharia values. Design/Methodology/Approach: This research employs a legal normative approach using a conceptual framework and statutory analysis. It examines the coexistence of state law and Islamic law within society to provide a comprehensive understanding of regulatory needs in sharia-based digital financing. Research Findings: The study finds that there are fundamental differences in the concept of lawful cause between conventional and sharia contracts. In conventional contracts, legal validity is determined by whether the agreement does not violate the law, morality, or public order. In contrast, sharia contracts must additionally ensure conformity with Islamic legal sources (the Qur’an and Sunnah). This difference underscores the need for a regulatory framework that accommodates both legal systems in digital financing platforms. Theoretical Contribution/Originality: This study contributes to the academic discourse by linking contract law theory with fintech practices, offering a deeper understanding of how dual legal systems state law and Islamic law can coexist in regulating digital financing. It expands the literature on sharia-compliant fintech governance and emphasizes the necessity of legal harmonization in the growing digital financial ecosystem. Practitioners/Policy Implications: The study highlights the necessity for the state to establish clear and integrated regulatory standards that ensure both legal and sharia compliance in digital financing. Strengthening supervision, certification, and compliance mechanisms is essential to prevent illegal fintech operations and protect consumers. Research Limitations/Implications: The research is conceptual and normative in nature, relying on legal analysis rather than empirical field data. Further empirical studies are encouraged to evaluate the implementation effectiveness of integrated sharia and conventional legal frameworks in fintech operations.